Lignocellulolytic materials-as a raw material for the production of fermentable sugars via solid state fermentation - L.S.Hong; Darah Ibrahim; Ibrahim Che Omar (2011)
The aim of this study was to explore possibility of utilizing agrowastes effectively to convert them into fermentable sugars by the production of in situ enzyme in solid state fermentation, which agrowaste can be used as substrates for the microbial fermentation in the production of commercial viable products. To enhance the usage of abundant agrowaste generated in Malaysia a study was cunducted in view of exploring the possibility of utilizing it effectively for the conversion to fermentable sugars.Agrowaste is rich of lignoselulolytic material which can serve as good substrate in solid state fermentation to produce the fermentable sugar.